Estructura de la negociación salarial e incentivos a innovar - Barcena-Ruiz, Juan Carlos; Campos, María Luz (Estudios de Economía, 2016)
In this article we analyse the effect that the sequence of salary negotiations has on the firm´s decisions about the adoption of new labour saving technologies. We show that if the cost of the innovation is sufficiently high, innovations are related with sequential as well with simultaneous negotiations. In addition, the cost of the innovation depends on the market size, increases in labour productivity resulting of the new technology and the reserve salary of workers.